(untitled) (Theatrum historiae, 2023)
The paper evaluates the representation of early modern economic history at the 12th congress of Czech historians in Ústí nad Labem in September 2022 and responds to opinions about the current decline of the discipline of economic history and its replacement by the “new” cultural history. It emphasises the continuing importance of classical economic history and the need to enrich it with new approaches, based on complexity, a comparative approach, and interdisciplinarity. Two historiographic probes demonstrating the meaning and significance of the study of territorial economic relations in the 16th and 17th centuries are presented. The first is a microhistorical insight into the management and function of the suburban estates of the Czech nobility in the immediate vicinity of the provincial capital, Prague, at the end of the 16th century, as can be observed through the example of the small manor of Košíř, owned in the years 1585–1597 by the lords of Hradec. The second probe shows the possibilities and benefits of analysing data from contemporary tax records and lists of serfdom duties and corvées for understanding the function and status of cities and towns in the South Bohemian domain of the lords of Hradec. It describes the structure of the urban network and the hierarchy of urban settlements in the 17th century, captures the original traces of war damage, and suggests the possibility of following the trends of early modern urbanisation in the territory of the former Bechyňsko region in a long wave from the end of the Thirty Years’ War to the beginning of industrialisation and the new “industrial” urbanisation in the 19th century.